The four agreements : a practical guide to personal freedom - Ruiz, Miguel, 1952- (San Rafael, Calif. : Amber-Allen Pub. : Distributed by Publishers Group West, 1997)
Presents advice on how to gain personal freedom by following the wisdom of the Toltecs.
Domestication and the dream of the planet -- The first agreement: be impeccable with your word -- The second agreement: don't take anything personally -- The third agreement: don't make assumptions -- The fourth agreement:always do your best -- The Toltec path to freedom: breaking old agreements -- The new dream: heaven on earth -- Prayers.
Keywords: Conduct of life; Toltec philosophy -- Miscellanea; Philosophy